2015
DOI: 10.7863/ultra.34.8.1455
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Intratendinous Injections With Platelet‐Rich Plasma or Autologous Whole Blood for Treatment of Proximal Hamstring Tendinopathy

Abstract: Both PRP and WB groups showed improvements in all outcome measures at 6 months. The PRP group showed significant improvements in 6-month ADL and IHOT-33 scores. The WB group reached significance in 15-minute sitting pain. No significant between-group differences were observed at any time point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 34 publications
(58 reference statements)
1
62
1
Order By: Relevance
“…PRP could provide several molecules capable of boosting healing mechanisms and counteracting degenerative processes in tendinopathic tendon, restoring tissue architecture and enhancing tenocyte viability. In the present review, initial evidences in favor of PRP injections have been found only in the management of hamstring tendinopathy 23,24 , while the efficacy of this treatment in the other hip tendinopathies is not investigated yet. However, the encouraging results obtained, may allow to an ulterior option prior to surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRP could provide several molecules capable of boosting healing mechanisms and counteracting degenerative processes in tendinopathic tendon, restoring tissue architecture and enhancing tenocyte viability. In the present review, initial evidences in favor of PRP injections have been found only in the management of hamstring tendinopathy 23,24 , while the efficacy of this treatment in the other hip tendinopathies is not investigated yet. However, the encouraging results obtained, may allow to an ulterior option prior to surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…No clinical complications were reported during follow-up. In a double blind RCT, PRP injections result equally effective to whole blood cell injections until 6 months of follow-up, without any statistically significance difference 24 . Zissen MH et al 25 in a retrospective study enrolled 65 patients who received ultrasound-guided corticosteroid injections between January 2002 and December 2008.…”
Section: Conservative Management Of Tendinopathies Around Hipmentioning
confidence: 99%
“…[37][38][39][40] When the studies in which PRP was obtained from autologous blood in clinics were considered, it was found that it was prepared from 10 to 20 min. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Nevertheless, it takes time to apply it to cases, which makes its bioactive and effective treatment results controversy.…”
Section: -2234mentioning
confidence: 99%
“…The cases in PRP group showed significant increase in ADL and IHOT-33 scoring during 6th month when compared to pre-injection, yet it was not the case in total blood applications. 10 In another manuscript, PRP and HA injected groups were compared in cases with osteoarthritis (n = 192). The cases were injected PRP and HA for the purpose of delay of surgery.…”
Section: -2234mentioning
confidence: 99%
See 1 more Smart Citation